2020
DOI: 10.1021/acs.jproteome.0c00303
|View full text |Cite
|
Sign up to set email alerts
|

PEPPI-MS: Polyacrylamide-Gel-Based Prefractionation for Analysis of Intact Proteoforms and Protein Complexes by Mass Spectrometry

Abstract: Prefractionation of complex mixtures of proteins derived from biological samples is indispensable for proteome analysis via top-down mass spectrometry (MS). Polyacrylamide gel electrophoresis (PAGE), which enables high-resolution protein separation based on molecular size, is a widely used technique in biochemical experiments and has the potential to be useful in sample fractionation for top-down MS analysis. However, the lack of a means to efficiently recover the separated proteins in-gel has always been a ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(79 citation statements)
references
References 60 publications
1
77
1
Order By: Relevance
“…These instruments can transmit large protein complexes without providing excessive activation that could compromise protein complex structure. In recent years, important progress in native purication methods such as native gel-eluted liquid fraction entrapment electrophoresis (GeLFrEE) separation, 36 native gel electrophoresis, 37 ion exchange chromatography (IEX), 38 hydrophobic interaction chromatography (HIC), 39,40 and online buffer exchange, has made these methods more applicable for complex mixtures and for characterisation of endogenous ligands. 36,41 By using appropriate sample preparation, ionisation conditions, and instrumentation, many challenging analytes such as membrane proteins, 18,42 intrinsically disordered proteins, 43 highly dynamic or heterogeneous complexes, 19 or very large systems such as intact virus capsids 44 can all be investigated using native MS, as well as their associated proteoforms.…”
Section: Native Mass Spectrometry Of Protein Complexesmentioning
confidence: 99%
“…These instruments can transmit large protein complexes without providing excessive activation that could compromise protein complex structure. In recent years, important progress in native purication methods such as native gel-eluted liquid fraction entrapment electrophoresis (GeLFrEE) separation, 36 native gel electrophoresis, 37 ion exchange chromatography (IEX), 38 hydrophobic interaction chromatography (HIC), 39,40 and online buffer exchange, has made these methods more applicable for complex mixtures and for characterisation of endogenous ligands. 36,41 By using appropriate sample preparation, ionisation conditions, and instrumentation, many challenging analytes such as membrane proteins, 18,42 intrinsically disordered proteins, 43 highly dynamic or heterogeneous complexes, 19 or very large systems such as intact virus capsids 44 can all be investigated using native MS, as well as their associated proteoforms.…”
Section: Native Mass Spectrometry Of Protein Complexesmentioning
confidence: 99%
“…In a very recent study by Takemori et al. [141], the authors showed increased recovery (∼75%) when using a novel approach based on a passive elution of intact proteins from polyacrylamide gels and the use of aqueous solvents. The intrinsic weakness of these approaches is also their poor resolving power for certain classes of proteins (i.e.…”
Section: Electrophoretic Methodsmentioning
confidence: 99%
“…Takemori and co‐workers [141] present in their recent study a novel workflow called Passively Eluting Proteins from Polyacrylamide gels as Intact species (PEPPI), which allows further top‐down MS identification of separated proteins. An illustration of this workflow is given in Figure 7.…”
Section: Electrophoretic Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The classic approach starts with the separation of proteins by 2-DE or LC prior to enzymatic digestion and LC-MS/MS analysis of the peptide digest [37]. The second strategy is applied in top-down proteomics, which allows the multi-dimensional separation in protein level, followed by MS/MS analysis [38]. The third method is widely used in bottom-up proteomics studies, which first digests the proteins into peptides prior to multi-dimensional separation and MS/MS analysis [39].…”
Section: Introductionmentioning
confidence: 99%